1975
DOI: 10.1063/1.430311
|View full text |Cite
|
Sign up to set email alerts
|

Ionization in the track of a high-energy electron in hydrocarbon liquids; study of positive and negative ion scavenging using nanosecond pulse radiolysis

Abstract: The lifetime distribution of the charged particles in the track of a high-energy electron in cyclohexane and isooctane has been considered. Results on the decay of biphenyl ions in solutions of biphenyl obtained by means of pulse radiolysis with nanosecond time resolution have been compared with lifetime distributions calculated from the concentration dependence of the steady state scavenging, using recently determined absolute rate constants for reaction of excess electrons and mobilities of the charged speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…This suggested a short life time for the solvent holes. The kinetic data on delayed fluorescence [49] and transient absorbance [6,20,25] in radiolysis of cyclohexane supported this conclusion. It was concluded that the lifetime of the solvent hole is only 20-30 ns [6,25], or 10 times shorter than the lifetime of the high-mobility cations observed in the conductivity experiments.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…This suggested a short life time for the solvent holes. The kinetic data on delayed fluorescence [49] and transient absorbance [6,20,25] in radiolysis of cyclohexane supported this conclusion. It was concluded that the lifetime of the solvent hole is only 20-30 ns [6,25], or 10 times shorter than the lifetime of the high-mobility cations observed in the conductivity experiments.…”
supporting
confidence: 53%
“…2.1 High mobility cations. Ionization of several cycloalkane liquids -cyclohexane, methylcyclohexane, trans-decalin and cis-decalin -produces cations whose drift mobilities are 5to-25 times greater than the mobilities of normally-diffusing molecular ions and (in some cases) thermalized electrons in these liquids [4][5][6][7][8]. These high-mobility cations are shown to be cycloalkane solvent holes with unusually long natural lifetimes (0.2 µs to 5 µs).…”
Section: S S S So O O Ol L L Lv V V Ve E E En N N Nt T T T H H H Ho O...mentioning
confidence: 99%
See 3 more Smart Citations